Проблемы образования как последствия темпа социокультурных трансформаций - I. V. Melik-Gaykazyan (Высшее образование в России, 2022)
Based on the information-synergetic approach the criterion of self-organization of educational systems was established (the result of the project RFBR № 11-06-00160), itdetects paradoxes and problems of management of education modernization (the result of the project RFBR № 10-06-00313). The concept of memory-turn allows to trace cultural determinations of bioethics principles (the result of the project RFH № 12-03-00198).